The Impact of Government Borrowing Costs on Fiscal Discipline. (15th March 2019) - Tkačevs, Oļegs; Vilerts, Kārlis
Summary: This paper studies the impact of government borrowing costs on fiscal discipline against the background of unprecedentedly low interest rates in advanced economies brought about by ultra‐expansionary monetary policies of recent years. Applying the panel data econometric approach for a sample of OECD and 11 early euro area countries over the period 1985–2015, the study suggests a positive and statistically significant impact of government borrowing costs on cyclically adjusted primary balances, indicating that a decrease in borrowing costs leads to a deterioration of fiscal policy stance. The findings herein also suggest that this effect in the euro area seems to be driven by a group of its peripheral rather than core countries and appears to work through the expenditure (more specifically, current expenditure) channel. From the economic policy perspective, these findings imply that monetary policy measures resulting in ultra‐low interest rates may cause negative side effects for fiscal discipline.